A new approach to determining the development directions for crop insurance organizations: experience from Lithuania - Drejeris, Rolandas; Rusteika, Martynas (Edelweiss Applied Science and Technology, 2024)
The appropriate organization of the crop insurance process is an essential task for all participants in the insurance system, and the system development is one of the main arguments for its existence. The main problem is that crop insurance companies do not have any instrument for determining the most suitable direction for development as an obligatory strategic solution. This article aims to provide the methodology suitable for insurance companies as participants in the crop insurance system to determine the most appropriate direction for development under the present conditions. In this article, we provide the substantiated multicriteria methodology for determining the most suitable direction for developing the activity performed by insurance companies. Insurance companies’ possible business development directions are justified, and appropriate evaluation criteria are specified. The suggested methodology is based on applying the multicriteria assessment method, TOPSIS. This original method proved to be the most suitable one for management solutions. This quantitative methodology was tested under natural conditions, using the example of Lithuania, and the suitability of its application was proved entirely. The suggested methodology can also help crop insurance companies find the best direction for future development.